NUTRITIONAL ASSISTANCE THROUGH DIARY NUTRIME APPLICATION ON ENERGY AND FAT INTAKE IN OVERWEIGHT AND OBESE ADOLESCENTS AT MAN TANJUNG BALAI - Haryana, Nila Reswari; Azbi, Cinta Maulida; Emilia, Esi; Sandy, Yatty Destani; Firmansyah, Hardi (Media Gizi Indonesia, 2025)
Overweight or obese adolescents tend to consume food without noticing its nutritional content, which results in food selection defects. Adolescent food intake requires full support from the media for nutritional assistance. This study aimed to determine the difference in energy and fat intake before and after nutritional assistance through Diary NutriMe application. This study applied a quasi-experimental method using a One Group Pretest-Posttest design. The participants in this study were 36 high school students from MAN Tanjung Balai who were overweight or obese and were selected by purposive sampling. All data were analyzed using a Paired Sample t-test for energy intake (distributed data were normal) and the Wilcoxon test for fat intake (distributed data were non-normal). This study found that the average energy intake after receiving nutritional assistance was 1440.9 ± 195.2 kcal, while the average fat intake was 36.8 ± 10.8 g. According to the paired sample t-test, a significant decrease (p = 0.000) in energy intake was observed after nutritional assistance through Diary NutriMe application. Similarly, the Wilcoxon test showed a significant decrease (P = 0.000) in fat intake after the intervention. Therefore, the Diary NutriMe application is suitable as a nutritional assistant to reduce energy and fat intake in overweight and obese adolescents in MAN Tanjung Balai.